2022
DOI: 10.1007/s10586-021-03514-x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving data privacy for decision support systems in times of massive data sharing

Abstract: The world is suffering from a new pandemic of Covid-19 that is affecting human lives. The collection of records for Covid-19 patients is necessary to tackle that situation. The decision support systems (DSS) are used to gather that records. The researchers access the patient’s data through DSS and perform predictions on the severity and effect of the Covid-19 disease; in contrast, unauthorized users can also access the data for malicious purposes. For that reason, it is a challenging task to protect Covid-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This can be achieved through many aspects to ensure that patients' sensitive data are used responsibly and are protected. In fact, it has been identified that the privacy of data is a major concern during the time of pandemics such as COVID-19 due to massive data sharing during this period (Fazal et al, 2022). The developed applications for mitigating COVID-19 such as contact tracing applications are among those applications over which there are concerns regarding data privacy (Mikkelsen et al, 2020;Zwitter and Gstrein, 2020).…”
Section: Challenges Associated With Ai Covid-19 Related Technologiesmentioning
confidence: 99%
“…This can be achieved through many aspects to ensure that patients' sensitive data are used responsibly and are protected. In fact, it has been identified that the privacy of data is a major concern during the time of pandemics such as COVID-19 due to massive data sharing during this period (Fazal et al, 2022). The developed applications for mitigating COVID-19 such as contact tracing applications are among those applications over which there are concerns regarding data privacy (Mikkelsen et al, 2020;Zwitter and Gstrein, 2020).…”
Section: Challenges Associated With Ai Covid-19 Related Technologiesmentioning
confidence: 99%
“…For this reason, some hospitals have developed codes of conduct that help doctors and nurses protect patients' privacy when using online platforms (Molnár-Gábor & Korbel, 2020). Hospitals also resort to these codes to update their online corporate communication initiatives and their branding strategies (Fazal et al, 2022). Finally, hospitals also implement training sessions for patients to help them understand how to use online platforms when they interact with doctors (Belani et al, 2021).…”
Section: Smart Reputation Managementmentioning
confidence: 99%
“…Fazal et al [ 27 ] recommended a decision support system to manage privacy while sharing massive amounts of data in a third-party environment. The authors used COVID-19 patients’ health information to analyze security.…”
Section: Literature Studymentioning
confidence: 99%